Preventing and managing the toxicities associated with the combination therapy of ibrutinib and venetoclax in chronic lymphocytic leukaemia - Elżbieta Iskierka-Jażdżewska; Krzysztof Jamroziak; Tadeusz Robak; Bartosz Puła (Acta Haematologica Polonica)
The combination of ibrutinib and venetoclax represents the first fixed-duration oral treatment involving a Bruton tyrosine kinase inhibitor and a BCL2 inhibitor for adult patients with untreated chronic lymphocytic leukaemia. The phase 2 CAPTIVATE and phase 3 GLOW clinical studies served as the basis for this approval. This combination demonstrates high efficacy, a limited duration of therapy, and a tolerable adverse event profile. However, some concerns have been raised regarding its tolerability based on the results of clinical trials. The risk of developing adverse events may be minimised by careful selection of patients, including preventive measures and rational management of therapy-associated toxicities. Therefore, we have summarised the published data from clinical trials and real-world observations to optimise the treatment outcomes and tolerability of the ibrutinib and venetoclax combination.